Mechanical and Thermal Analysis of Cissus Quadrangularis Stem Fiber/Epoxy Composite with Micro-Red Mud Filler Composite for Structural Application - Gandhi, V. C. Sathish; Jenish, I.; Indran, S.; Rajan, D. Yugendra (Transactions of the Indian Institute of Metals, 2022)
The Cissus quadrangularis stem fiber (CQSF)-reinforced epoxy composite particulate filled with micro-red mud has been fabricated, and the mechanical and thermal behaviors have been investigated. The different compositions of the samples were prepared by the hand layup method. The base material was prepared with the composition of epoxy resin and 30 wt% CQSF at 40 mm of fiber length. Excluding base material, four more samples have been prepared by adding filler material at 2.5, 5, 7.5, and 10 wt%. The tensile and flexural strength of the materials increased up to 5 wt% addition of red mud and reduced thereafter, whereas the hardness increased gradually with the addition of filler content. The maximum energy absorption capacity was obtained at 7.5 wt% red mud addition. The highest char production was achieved at 10 wt% red mud filler addition, according to thermogravimetric analysis (TGA). The optimized wear and mechanical characteristics were supported by scanning electron microscope (SEM) pictures of the mechanically broken surfaces.